Beloved captive [large type] - Y'Barbo, Kathleen (Fairweather Key, 2010)
"Emilie Gayarre grew up in luxury but left it all for a safe haven on the isolated island of Fairweather Key, where she has made a new life for herself as a schoolteacher. But now she has been called home to New Orleans and her father's deathbed only to learn the life she was raised to enjoy was all a lie. A stigma attached to her birth could steal any hope for a happy future..."--Book jacket.